OBSERVATION OF DISTRIBUTION AND QUALITATIVE PROPERTIES OF HORSELIVESTOCK (EQUUSCABALLUS) IN NORTH SUMATRA - A Gultom; Hamdan Hamdan; M Tafsin; S Umar; A H Daulay (Universitas Sumatera Utara, 2017)
Abstract. This study aims to determine the spread of horses and horses based on the observation of the color of feathers, facial marks, foot shape and back shape in Humbang Hasundutan, Samosir, Karo and North Tapanuli districts. This research was conducted in July-September 2016 by performing phenotypic analysis (color and face mark) at 271 horses in Humbang Hasundutan District, Samosir Regency, Karo Regency and North Tapanuli Regency. The research method used is survey method and Simple Random Sampling method (simple random sampling) done to determine the cattle that will be used as sample. The analysis shows that horses in North Sumatera have various color and dominant red brown (27,86%). Horses in North Sumatra have various dominant faces that dominate strike (54.95%). Keywords : distribution, qualitative, horselivestock